Effect of Board Diversity on Financial Performance of the Vietnamese Listed Firms - Ngo, My Tran; Pham, Thi Hong Van; Luu, Thi Thai Tam (Asian Economic and Financial Review, 2019)
This study investigated the impact of board diversity on the financial performance of listed firms on the Vietnamese stock exchange. Four demographic characteristics of board members (gender, nationality, level of education and level of age) were used as the proxies for diversity. The data were analyzed by different methods including Pooled OLS regression, Fixed Effect Model (FEM), Random Effect Model (REM) and Generalized Method of Moments (GMM) using a sample of 482 companies listed in the period from 2015 to 2017. The results showed that the percentages of female members, foreign members and members with post-graduate degrees on the board, were statistically associated with improvement in financial performance. However, there was no evidence that the percentage of members under 45 years old on the board affected the performance of listed firms on the Vietnamese stock exchange.